2019
DOI: 10.1093/comnet/cnz012
|View full text |Cite
|
Sign up to set email alerts
|

The multiplex structure of the mental lexicon influences picture naming in people with aphasia

Abstract: An emerging area of research in cognitive science is the utilization of networks to model the structure and processes of the mental lexicon in healthy and clinical populations, like aphasia. Previous research has focused on only one type of word similarity at a time (e.g., semantic relationships), even though words are multi-faceted. Here, we investigate lexical retrieval in a picture naming task from people with Broca’s and Wernicke’s aphasia and healthy controls by utilizing a multiplex network structure tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…Multiplex networks represent a natural and suitable framework for this purpose, as they simultaneously encode multiple types of interaction among units of a complex networked system [49]. Therefore, multiplex lexical networks can be used to extract information about linguistic structures beyond information available from single-layer network analysis [9,[50][51][52][53].…”
Section: Beyond Semantics: a Multiplex Approach To Study The Mental Lmentioning
confidence: 99%
See 4 more Smart Citations
“…Multiplex networks represent a natural and suitable framework for this purpose, as they simultaneously encode multiple types of interaction among units of a complex networked system [49]. Therefore, multiplex lexical networks can be used to extract information about linguistic structures beyond information available from single-layer network analysis [9,[50][51][52][53].…”
Section: Beyond Semantics: a Multiplex Approach To Study The Mental Lmentioning
confidence: 99%
“…The authors showed that the multiplex combination of different aspects of semantics and phonology boosted the lure of associates, a phenomenon where children tend to acquire new words that are similar to ones they already know, thus making the multiplex lexical representation of words in the mental lexicon a suitable tool for predicting early word acquisition [9,50,52]. The multiplex interplay between semantic, syntactic and phonological similarities of words also highlighted phonological priming effects [53] and critical differences in picture naming performance in patients with aphasia [51], a clinical condition affecting language understanding and production. Furthermore, examining the structure of this multiplex lexicon revealed a core of words that are highly connected to each other [10].…”
Section: Beyond Semantics: a Multiplex Approach To Study The Mental Lmentioning
confidence: 99%
See 3 more Smart Citations